Coordination of macroeconomic policies? Latin American challenges and dilemmas - González-Vigil, Fernando (1994)
This paper examines the "spontaneous" process of macroeconomic policy convergence which is currently taking place in Latin America. Deepening the ongoing structural change requires dealing with its microeconomic and institutional issues. This in turn implies that countries in the region internalize the need for reform and its final goals, and enhance their "endogenous" capacity for managing economic policy matters. However, this capacity is being eroded by the growing processes of globalization and interdependence, which also affect developed countries. The forming of "regional blocks" appears to be a way for regaining as a group, the economic autonomy that has been lost individually. In such a context, this paper analyses the possibilities and limitations for Latin American countries in undertaking systematic efforts of economic policy "endogenous" coordination among them, in the framework of the existing regional integration agreements.